Serum chitotriosidase in postmenopausal women with severe osteoporosis. Issue 2 (February 2016) - Musumeci, M.; Palermo, A.; D'Onofrio, L.; Vadalà, G.; Greto, V.; Di Stasio, E.; Maddaloni, E.; Di Rosa, M.; Tibullo, D.; Silvia, A.; Napoli, N.; Denaro, V.; et al.
Abstract Summary Human chitotriosidase (Chit) increases during the osteoclast differentiation and their activity. We demonstrated that serum Chit was significantly higher in osteoporotic subjects than in healthy control ones and revealed a negative correlation between Chit and bone mineral density (BMD). This is the first study showing a correlation between Chit and severe postmenopausal osteoporosis. Introduction Mammalian chitinases exert important biological roles in the monocyte lineage and chronic inflammatory diseases. In particular, Chit seems to promote bone resorption in vitro. No in vivo studies have been performed to confirm this finding. We aim to evaluate Chit activity in postmenopausal women affected by severe osteoporosis. Methods In this cross-sectional study, 91 postmenopausal women affected by osteoporosis and 61 with either osteopenia or normal BMD were screened. All subjects were assessed by dual-energy X-ray absorptiometry (DXA) and X-ray vertebral morphometry. Osteoporotic subjects were considered eligible if they were affected by at least one vertebral osteoporotic fracture (group A = 57 subjects). Osteopenic or healthy subjects were free from osteoporotic fractures (group B = 51 subjects). Enzymatic Chit and serum β-CrossLaps (CTX) were measured in the whole population. Results Group A showed higher serum levels of beta-CTX compared to group B (0.40 ± 0.26 ng/mL vs 0.29 ± 0.2 ng/mL, p = 0.022). Chit was significantly higher in group A than in group B (1042 ± 613 nmol/mL/h vs 472 ± 313 nmol/mL/h, p < 0.001, respectively) even after adjustment for age (p < 0.001). Spearman correlation test revealed a negative correlation between Chit and BMD at each site (lumbar spine: r = −0.38, p = 0.001, femoral neck: r = −0.35, p = 0.001, total femur: r = −0.39, p < 0.001). Furthermore, a positive correlation between Chit and PTH was observed (r = 0.26, p = 0.013). No significant correlation was found between Chit and beta-CTX (r = 0.12, p = 0.229). After a multivariate analysis, a positive correlation between severe osteoporosis and Chit (p < 0.001), beta-CTX (p = 0.013), and age (p < 0.001) was observed. Conclusion This is the first clinical study showing a correlation between Chit and severe postmenopausal osteoporosis. Larger and prospective studies are needed to evaluate if Chit may be a promising clinical biomarker and/or therapeutic monitor in subjects with osteoporosis.